(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
In the article, the issue of increasing depopulation processes in Poland and Europe as a result of social changes including changes of procreative attitudes has been dis-cussed. Essential meaning in designing the procreative activity has the dominant family model as well as the family policy from the state.